1993
DOI: 10.1152/jn.1993.69.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Organization of response areas in ferret primary auditory cortex

Abstract: 1. We studied the topographic organization of the response areas obtained from single- and multiunit recordings along the isofrequency planes of the primary auditory cortex in the barbiturate-anesthetized ferret. 2. Using a two-tone stimulus, we determined the excitatory and inhibitory portions of the response areas and then parameterized them in terms of an asymmetry index. The index measures the balance of excitatory and inhibitory influences around the best frequency (BF). 3. The sensitivity of responses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
201
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(213 citation statements)
references
References 47 publications
11
201
1
Order By: Relevance
“…This is the opposite of what would be expected from neuronal adaptation. One possible mechanism that is consistent with this narrowing of sustained responses could be lateral inhibition, which has been shown to be present at multiple levels of central auditory processing (Shamma et al 1993;Ramachandran et al 1999;Young 2003). One implication of this narrowing of sustained responses is that comparisons of psychophysical and electrophysiological measures (for example, ECAPs) in CI users should ideally be made using similar pulse rates.…”
Section: Fig 15mentioning
confidence: 71%
“…This is the opposite of what would be expected from neuronal adaptation. One possible mechanism that is consistent with this narrowing of sustained responses could be lateral inhibition, which has been shown to be present at multiple levels of central auditory processing (Shamma et al 1993;Ramachandran et al 1999;Young 2003). One implication of this narrowing of sustained responses is that comparisons of psychophysical and electrophysiological measures (for example, ECAPs) in CI users should ideally be made using similar pulse rates.…”
Section: Fig 15mentioning
confidence: 71%
“…Using complex stimuli, such as dynamic ripples and natural sounds, it is possible to derive the neuronal population preference to spectrotemporal acoustic properties beyond frequency (39). Together with those stimuli, the methods used here can be exploited to investigate cortical depth stability or laminar variability of neuronal population tuning to other acoustic features, such as spectral and temporal modulations, aural dominance and binaural interaction, and frequency sweep direction (10,11,16). Finally, this study provides the basis for investigating neuronal population receptive field changes during increasingly complex auditory and multisensory tasks.…”
Section: Discussionmentioning
confidence: 99%
“…These anatomical observations of cortical microcolumns inspired invasive electrophysiological investigations in cats (7), demonstrating that frequency preference is constant across cortical depth (i.e., frequency columns). Since this early study, frequency columns have been observed in a variety of animals (3,(8)(9)(10), and a columnar organization has been suggested for other acoustic properties (10, 11). Despite this anatomical and physiological evidence from animal models, the role of cortical columns in auditory perception is not understood (6, 12, 13).…”
mentioning
confidence: 99%
“…In the central nervous system, studies that use acoustic stimuli show interchannel interaction in the form of lateral (or twotone) inhibition. Two-tone inhibition has been demonstrated in the cochlear nucleus (e.g., Young 1998), the inferior colliculus (e.g., Ramachandran et al 1999), and the auditory cortex (e.g., Shamma et al 1993). In our studies, even the most restricted electrical stimuli (i.e., TP configuration) activate cortical regions as large as those activated in normalhearing guinea pigs by 1-octave-wide noise bands (Arenberg et al 2000;Bierer and Middlebrooks 2002;present study).…”
Section: Possible Mechanisms Of Channel Interactionmentioning
confidence: 99%